GREEN TECHNOLOGY DYNAMISM, GREEN ENTREPRENEURIAL ORIENTATION AND FINANCIAL CAPABILITY FOR ENHANCING MSMEs’ FINANCIAL PERFORMANCE: GREEN TECHNOLOGY DYNAMISM, GREEN ENTREPRENEURIAL ORIENTATION AND FINANCIAL CAPABILITY FOR ENHANCING MSMEs’ FINANCIAL PERFORMANCE - Aunurrafiq, Aunurrafiq; Kamaliah, Kamaliah; Badriyah, Nurul (Universitas Riau, 2025)
This study aims to examine and analyze the impact of green entrepreneurial orientation and financial capability on the financial performance of Micro Small and Medium Enterprises (MSMEs), while also assessing the moderating role of green technology dynamism on the relationship between green entrepreneurial orientation and financial performanceThis quantitative study employs a questionnaire-based data collection method, with questionnaires distributed directly to respondents. The sample consists of 217 MSME actors located in Siak District, Siak Regency. The results demonstrate that green entrepreneurial orientation and financial capability significantly influence the financial performance of MSMEs. Thi results are expected to contribute valuable insights for MSME actors, highlighting the importance of green entrepreneurial orientation and financial capability in enhancing financial performance. MSMEs with green entrepreneurial orientation and financial capability are better equipped to innovate, take proactive measures, and embrace risk to improve financial performance, all while considering economic, social, and environmental aspects within their operational context